The Design and Implementation of Administrative Controls: A Guide for Financial Executives. - Michenzi, Alfred R.; Moriarty, Shane R. (The Accounting Review, 1990)
Abstract Reviews the book `The Design and Implementation of Administrative Controls: A Guide for Financial Executives,' by John P. Fertakis.